Assessment of parameters influencing the electro activated, water character and explanation of process mechanism - Turkay, Ozge; Barisci, Sibel; Dimoglo, Anatoli (Inst Chemical Engineers, 2016)
The physicochemical properties of electro activated water (EAW) are highly affected by process conditions. In this context, the effects of parameters such as brine concentration, electrolysis time and current for EAW generation have been investigated using Response Surface Methodology (RSM). The predictive model for each response had high accuracy relative to R-2 values, namely, 0.85 for the oxidation reduction potential (ORP) and 0.94 for the free chlorine concentration (FCC). According to results, the brine concentration was the most significant factor that affected EAW character. Moreover, electrolysis time and brine concentration have synergetic effect on FCC. The mechanism of the EAW production was evaluated through the cyclic voltammogram (CV) of different brine concentrations on the graphite electrode. With the concentration increased anodic and cathodic peaks could be observed notably. Possible reaction pathways were evaluated on the cathode and anode sides. The formation of Cl-2, O-2, H-2, Cl-, OH-, H+ were determined by CV measurements. (C) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Electro activated water; Free chlorine; Response surface methodology; Cyclic voltammetry; Anolyte; Catholyte